Carbon monoxide releasing molecule 401 (CORM-401) modulates phase I metabolism of xenobiotics. (September 2019) - Walter, Moritz; Stahl, Wilhelm; Brenneisen, Peter; Reichert, Andreas S.; Stucki, David
Abstract: Next to its well-studied toxicity, carbon monoxide (CO) is recognized as a signalling molecule in various cellular processes. Thus, CO-releasing molecules (CORMs) are of considerable interest for basic research and drug development. Aim of the present study was to investigate if CO, released from CORMs, inhibits cytochrome P450-dependent monooxygenase (CYP) activity and modulates xenobiotic metabolism. CORM-401 was used as a model CO delivering compound; inactive CORM-401 (iCORM-401), unable to release CO, served as control compound. CO release from CORM-401, but not from iCORM-401, was validated using the cell free myoglobin assay. CO-dependent inhibition of CYP activity was shown by 7-ethoxyresorufin- O -deethylation (EROD) with recombinant CYP and HepG2 cells. Upon CORM-401 exposure EROD activity of recombinant CYP decreased concentration dependently, while iCORM-401 had no effect. Treatment with CORM-401 decreased EROD activity in HepG2 cells at concentrations higher than 50 μM CORM-401, while iCORM-401 showed no effect. At the given concentrations cell viability was not affected. Amitriptyline was selected as a model xenobiotic and formation of its metabolite nortriptyline by recombinant CYP was determined by HPLC. CORM-401 treatment inhibited the formation of nortriptyline whereas iCORM-401 treatment did not. Overall, we demonstrate CO-mediated inhibitory effects on CYP activity when applying CORMs. Since CORMs are currently under drug development, the findings emphasize the importance to take into account that this class of compounds may interfere with xenobiotic metabolism. Graphical abstract: Unlabelled Image Highlights: CORM-401 inhibits EROD activity of recombinant CYP enzymes and living HepG2 cells. Inhibition of CYP enzyme activity by CORM-401 is CO-mediated. CO from CORM-401 also inhibits xenobiotic metabolism of a model drug.